Customer Satisfaction And Customer Retention Towards Retail Store In Malaysia - P., Dinesh; A., Norida; H.M.R., Ali (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Business success in today’s competitive markets requires a great understanding and respect of the customer. This paper will discuss more on the factors influencing customer satisfaction and customer retention towards retail stores in Malaysia. Therefore, few factors such as promotional mix, service quality, psychological and product quality take into consideration. Kano model and Maslow’s Hierarchy of Needs theory is focused in this study to provide clear understanding about this research.